Restoring the Chilean Race: Catholicism and Latin Eugenics in Chile - Walsh, Sarah ca. 20:/21. Jh. (The catholic historical review, 2019)
Using early twentieth century Chile as a case study, this article examines the interaction between Catholicism and eugenic social reform in Latin America. Examining articles that appeared in popular and Catholic periodicals between 1891 and 1940, it argues that both Catholic and secular eugenicists advocated for the modernization of patriarchal social structures to protect the racial health of the Chilean population. The article therefore illustrates how Latin American eugenics, though less concerned with biological heritage than its North American counterparts, still supported the notion that organizing societies around gender difference was scientifically sound.